Evaluación de tres variedades de caña de azúcar (Saccharum officinarum) y su efecto sobre las características agronómicas y su rendimiento como forraje en el fundo Zungarococha, San Juan Bautista- 2018 - Pïnedo Amaringo, Ronald (2021)
The research work was carried out at the National University of the Peruvian Amazon at the Faculty of Agronomy in the cattle workshop in the Zungarococha Farm, entitled EVALUATION OF THREE VARIETIES OF SUGAR CANE (Saccharum officinarum) AND THEIR EFFECT ON THE AGRONOMIC CHARACTERISTICS AND ITS YIELD AS FORAGE IN THE ZUNGAROCOCHA FUND, SAN JUAN BAUTISTA - 2018. The evaluations were carried out sixteen weeks after sowing with vegetative seed (cuttings), in plots of 5 mx 2 m (10 m2) and an experimental of 495 m2. With a Random Complete Block Design (D.B.C.A), with four treatments and four repetitions, the treatments under study were: T0 (Pennisetum sp cv King grass green), T1 (Saccharum officinarum Var. Yellow), T2 (Saccharum officinarum Var. Black) and T3 (Saccharum officinarum Var. Ash), obtaining the following results: In the production of green plant matter Whole, the Yellow cane variety (T1), achieved the highest average with 9.66 kg / m2, followed by T2 (Black variety) with 9.37 kg / m2 and T3 (Ash variety) with 9.16 kg / m2 but statistically they are homogeneous. In the yield of green matter per hectare (t / ha.), The yellow variety achieved 96.63 t, however, the three varieties of cane do not differ statistically, which is below the national average that is 100 t / ha.